Survival Rates of Patients with Non-Small Cell Lung Cancer Depending on Lymph Node Metastasis: A Focus on Saliva - Lyudmila V. Bel’skaya; Elena A. Sarf; Victor K. Kosenok (Diagnostics, 2021)
The aim of this study was to compare overall survival (OS) rates at different pN stages of NSCLC depending on tumor characteristics and to assess the applicability of saliva biochemical markers as prognostic signs. The study included 239 patients with NSCLC (pN0-120, pN1-51, pN2-68). Saliva was analyzed for 34 biochemical indicators before the start of treatment. For pN0, the tumor size does not have a prognostic effect, but the histological type should be taken into account. For pN1 and pN2, long-term results are significantly worse in squamous cell cancer with a large tumor size. A larger volume of surgical treatment reduces the differences between OS. The statistically significant factors of an unfavorable prognosis at pN0 are the lactate dehydrogenase activity <1294 U/L and the level of diene conjugates >3.97 c.u. (HR = 3.48, 95% CI 1.21–9.85, p = 0.01541); at pN1, the content of imidazole compounds >0.296 mmol/L (HR = 6.75, 95% CI 1.28–34.57, p = 0.00822); at pN2 levels of protein <0.583 g/L and Schiff bases >0.602 c.u., as well as protein >0.583 g/L and Schiff bases <0.602 c.u. (HR = 2.07, 95% CI 1.47–8.93, p = 0.04351). Using salivary biochemical indicators, it is possible to carry out stratification into prognostic groups depending on the lymph node metastasis.